Perubahan Sosial Dalam Kodifikasi Hukum Adat Antara Stabilitas dan Perubahan Tata Hukum - Yamin - (Fakultas Hukum Universitas Mataram, 2016)
Each text undoubtedly has konsteks. Codified law, including customary law documented, also tend to reflect social change. In this context the law is within the two pairs of values, the values ​​of certainty and value changes. Codification of the law is an effort to ensure the validity of the juridical. Thus, the stability condition is reflected by codification norms. However, the sociological context is dynamic walking. In the context of the legal codification sociological change can be viewed in the constellation of the legal system. So it may be reflected in the codification of its social change.